2017
DOI: 10.12659/msm.903795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Rotation Correction of the Main Thoracic Curve in Severe Adolescent Idiopathic Scoliosis: Bending and Traction vs. Fulcrum – A Preliminary Report

Abstract: BackgroundFlexibility evaluation methods were only used to assess the changes of coronal Cobb angle in patients with adolescent idiopathic scoliosis (AIS). Little attention was attached to the vertebral rotation in these methods.Material/Method21 patients with severe adolescent idiopathic scoliosis were enrolled in this study. Coronal flexibility and rotation correction were compared on the supine bending, traction and fulcrum bending radiographs. The apical vertebral body rib ratio (AVB-R), and Perdriolle rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…On the one hand, the longitudinal distraction of the spine itself could produce a derotation effect. [17][18][19] Jhaveri et al reported that the overall mean AVR, as measured using the Nash-Moe scale, of the major structural curve was 3.1 AE 0.8 preoperatively, and it was reduced to 2.4 AE 0.6 intraoperatively following skeletal (skull femoral) traction for the correction of large-magnitude idiopathic and neuromuscular scoliosis. 20 The MSDR system performs internal longitudinal distraction on the scoliotic spine and may produce stronger traction that is more conducive to the correction of vertebral rotation.…”
Section: Corrective Effect Of Multiple Screw Distraction Reducermentioning
confidence: 99%
“…On the one hand, the longitudinal distraction of the spine itself could produce a derotation effect. [17][18][19] Jhaveri et al reported that the overall mean AVR, as measured using the Nash-Moe scale, of the major structural curve was 3.1 AE 0.8 preoperatively, and it was reduced to 2.4 AE 0.6 intraoperatively following skeletal (skull femoral) traction for the correction of large-magnitude idiopathic and neuromuscular scoliosis. 20 The MSDR system performs internal longitudinal distraction on the scoliotic spine and may produce stronger traction that is more conducive to the correction of vertebral rotation.…”
Section: Corrective Effect Of Multiple Screw Distraction Reducermentioning
confidence: 99%
“…2 In their classifications, King 3 and Lenke 4 highlighted the importance of the flexibility of the curves in the radiographical examination, formulating the concept of curve structurality and defining it as one of the most important parameters for surgical planning, responsible for the choice of arthrodesis levels and the number of corrective osteotomies. [5][6][7][8][9] Flexibility can be analyzed by several methods: bending in the standing or dorsal horizontal decubitus positions, fulcrum bending, traction, traction under general anesthesia, among others. [5][6][7][10][11][12] Currently, bending radiographs are considered the gold standard for flexibility assessment, because they are easy to perform and are one of the parameters included in the classifications.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Flexibility can be analyzed by several methods: bending in the standing or dorsal horizontal decubitus positions, fulcrum bending, traction, traction under general anesthesia, among others. [5][6][7][10][11][12] Currently, bending radiographs are considered the gold standard for flexibility assessment, because they are easy to perform and are one of the parameters included in the classifications. 5,7,13,14 It is known that in curves greater than 60 degrees traction is better than the other methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations